Analisis Laporan Keuangan untuk Menilai Kinerja Keuangan Sebelum dan Sesudah Pandemi pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Hutagaol, Adrian Michel H; Prayudi, Ahmad; Amelia, Wan Rizca (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The aim of this research is to find out how the financial performance of four banking companies listed on the Indonesia Stock Exchange was before and after the Covid 19 virus pandemic. The type of data used in this research is secondary data, namely research data sources obtained and collected by researchers indirectly, but with other parties. The data collection technique in this research is documentation technique. In this research, researchers used the paired samples T-Test as a tool to hypothesize in this research. Based on the results of the T-Test samples, the financial performance of PT Bank Rakyat Indonesia Tbk. Based on the liquidity ratio through current calculations and the quick ratio experienced a significant decrease. The financial performance of PT Bank Rakyat Indonesia Tbk based on the solvency ratio through calculating the debt to asset ratio and debt to equity ratio has increased significantly. The financial performance of PT Bank Rakyat Indonesia Tbk based on the activity ratio through calculating total asset turnover experienced a significant increase. Financial performance of PT Bank Central Asia Tbk. Based on the profitability ratio through the calculation of return on investment, it has decreased significantly and based on the calculation of return on Equity, PT Bank Mandiri Tbk has experienced a significant increase. Keywords: Activity Ratio, Liquidity Ratio, Profitability Ratio, Solvency Ratio.